Starch nanogels as promising drug nanocarriers in the management of oral bacterial infections - Saracoglu, Pelin; Dokuz, Senanur; Ozbek, Tulin; Topuzogullari, Murat; Ozmen, Mehmet Murat (ELSEVIER, 2023)
Nanogels, cross-linked nano-sized polymer networks with swelling properties are attracting increasing attention as bioactive delivery agents due to their large surface area and high loading capacity. In particular, polysaccharide nanogels are promising biomaterials in drug delivery and antibacterial applications. In this study, new nanogels were synthesized as antibacterial agent nanocarriers for the management of bacterial infections such as oral mucositis by crosslinking starch with polyethylene glycol digylcidyl ether (PEGDE). The structure, morphology, encapsulation efficiency, loading capacities, in vitro release as well as the antibacterial activity of the nanogels were investigated. The in vitro release and antibacterial activity tests were carried out in simulated saliva. The results revealed that the bare nanogels (BNG) and vancomycin loaded nanogels (VNG) exhibited hydrodynamic diameters below 100 nm. 70% of the loaded vancomycin was released from the nanogel in 15 min indicating that the nanogels exhibit a release profile within the range suitable for oral mucositis treatment. Moreover, the nanogels were biodegraded in 120 min, which is appropriate for rapid drug release approaches. Broth microdilution analysis showed that the VNG nanogels exhibit remarkable antibacterial activity with MIC values of 1.10 mu g/ml for S. aureus, and 8.80 mu g/ml for S. pyogenes and S. mutans. Hence, it was revealed that these nanogels are effective antibacterial nanomaterials against pathogens of oral mucositis infections. The novel starch nanogels are promising nanocarriers for drugs/bioactive agents in pharmaceutical and biotechnology industries.
Keywords: Antibacterial; Drug delivery; Nanogel; Starch; Oral mucositis; Vancomycin; NANOPARTICLES; HYDROGELS; Pharmacology & Pharmacy